2008
DOI: 10.1016/j.jmb.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Hinge Stiffness Is a Barrier to RNA Folding

Abstract: Cation-mediated RNA folding from extended to compact, biologically active conformations relies on a temporal balance of forces. The Mg2 +-mediated folding of the Tetrahymena thermophila ribozyme is characterized by rapid nonspecific collapse followed by tertiary-contact-induced compaction. This article focuses on an autonomously folding portion of the Tetrahymena ribozyme, its P4-P6 domain, in order to probe one facet of the rapid collapse: chain flexibility. The time evolution of P4-P6 folding was followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 36 publications
3
69
0
Order By: Relevance
“…Overall, the P4-P6 kinetic and thermodynamic constants obtained by smFRET measurements agree well with those obtained by multiple bulk approaches, including hydroxyl radical footprinting, stopped-flow fluorescence with a pyrene label, and small angle x-ray scattering (41)(42)(43)(44). Nevertheless, although some of these approaches provide additional structural information, none can match smFRET for the range of conditions that can be investigated, and the ease at which reversible folding can be followed.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Overall, the P4-P6 kinetic and thermodynamic constants obtained by smFRET measurements agree well with those obtained by multiple bulk approaches, including hydroxyl radical footprinting, stopped-flow fluorescence with a pyrene label, and small angle x-ray scattering (41)(42)(43)(44). Nevertheless, although some of these approaches provide additional structural information, none can match smFRET for the range of conditions that can be investigated, and the ease at which reversible folding can be followed.…”
supporting
confidence: 66%
“…1, A and B). P4-P6 was the first RNA with a side-by-side arrangement of helices to have its structure elucidated by x-ray crystallography and has been the subject of numerous folding studies (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The knowledge provided by these prior studies along with its relative simplicity, with only two long-range tertiary interactions, render P4-P6 an attractive target for addressing the general issue of complexity in RNA folding.…”
mentioning
confidence: 99%
“…The folding of P4-P6 has been followed in multiple studies, with folding rate constants of 2-30 s −1 observed across a range of conditions (52)(53)(54)(55)(61)(62)(63)(64)(65). However, interpretation of these overall rate constants has been stymied by a lack of knowledge of which individual folding steps were followed and rate limiting.…”
Section: Resultsmentioning
confidence: 99%
“…The control afforded by this well-behaved, established system provides an opportunity to deepen understanding and develop and test generalizable principles beyond this model system, provided that a detailed framework is in place to provide context for interpretation. Here, we use single-molecule FRET (smFRET) with a series of P4-P6 mutants to isolate and measure specific folding transitions, extending beyond measurements of overall folding rates (52)(53)(54)(55)(61)(62)(63)(64)(65) and constructing a kinetic and thermodynamic framework for P4-P6 RNA. This framework defines a preferred folding pathway, allows this pathway and the partitioning of states to be interpreted in structural terms, helps to uncover the origin of the effects of mutations on folding rates and pathways, and suggests a generalized framework for considering RNA tertiary folding.…”
mentioning
confidence: 99%
“…Understanding the kinetics, such as the rate and pathways for the conformational changes, is critical for deciphering the mechanism of RNA function (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Extensive experimental and theoretical studies on RNA folding kinetics have provided significant insights into the kinetic mechanism of RNA functions (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, due to the complexity of the RNA folding energy landscape (37)(38)(39)(40)(41)(42)(43)(44)(45)(46) and the limitations of experimental tools (47)(48)(49)(50)(51)(52)(53)(54)(55), many fundamental problems, ...…”
mentioning
confidence: 99%